Implementasi Information Retrieval System Aksesibilitas Buku di Perpustakaan dengan Metode Dice Similarity - Vika Ummu Hani; Syarifah Putri Agustini Alkadri; Rachmat Wahid Saleh Insani (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The problem of accessibility and efficiency of book search is still a major challenge in school libraries, especially those that still rely on manual systems. This study aims to implement and test the effectiveness of an information retrieval system (IRS) based on the Dice Similarity method in the SMA Negeri 1 Siantan Library, West Kalimantan. The research method used is experimental descriptive quantitative, with data collection through observation, interviews, and documentation, as well as system testing on collection data and library user activities. The system was developed using the Laravel framework and MySQL database, and evaluated using precision and recall metrics. The results showed that the system has a Precision value of 100% and a variable Recall value, with the highest value of 66.66% and the lowest of 14.28%. The implementation of this system significantly speeds up the search process, minimizes recording errors, and increases user satisfaction. The findings recommend the adoption of Dice Similarity-based IRS as an applicable solution for school libraries in supporting literacy and easy access to information. The findings are expected to be a reference for the development of library information systems in educational environments with limited resources.